(untitled) (Literatures of the World: Poetics, Mentality and Spirituality, 2017)
Vira Aheeva’s reception of O. Dovzhenko’s creative figure was represented in the article. It was formed on the basis of a comprehensive study of the artist’s diary, letters, archival materials and other relevant documents pertaining to his biography. Thoughts of Vira Aheeva are deeply reflective and controversial in some aspects. They represent “pure” Dovzhenko without shortcuts that are usual for him, which varied in different times, but had not fully reflected the many-sided personality of the author. The reflections of Vira Aheeva are filled with profound conclusions and generalizations of autobiographical discourse if the outstanding creator.